KEBIJAKAN DEVIDEN, HUTANG, INVESTASI DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Zulin Nur Faridah (Journal of Business & Banking, 2012)
It is a fact that the policy related to dividends in any company. is deemed very crucial. For that reason, research on this matter is considered important. This study attempts to find out the influence of dividend policy, debt policy, and investment policy toward the firm value in manufacture industries which were listed in Indonesia Stock Exchange. The data were collected from the companies which were listed in Indonesia Stock Exchange during the period of 2004 to 2008. Such data were collected through purposive sampling, with statistic method of F- analysis and t-analysis. The result of empirical examination with the analysis provided the fact as the following. (1) Dividend Policy, Debt Policy and Investment Policy had influence on the firm value. (2) Dividend Poticy factor had positive effect on firm value factor. (3) Debt policy factor had a negative effect on to Firm Value factor. (4) Investment policy factor had a negative influence toward firm value factor.